Methane production from sewage sludge treatment by ultrasonicated membrane anaerobic system (UMAS) - Egbal Hassan, Altoum Mohammed (2015)
Sewage Sludge wastewater causes serious environmental pollution due to its high chemical oxygen demand (COD) and biological oxygen demand (BOD). Traditional methods of treating sewage sludge wastewater are disadvantages from both economic and environmental perspectives. In this study, the potentials of Ultrasonicated Membrane Anaerobic System (UMAS) in treating wastewater as an alternative and cost effective method was investigated. Waste sludge samples used in the study were collected from sewage treatment plant of INDAH WATER in Kuantan, Malaysia. The temperature during collection of the raw sewage sludge was 32°C. The wastewater was stored in a cold room at 4°C prior to use The study began with some characterization studies to provide understanding of fundamental issues such as conventional separation, ultrasonic and membrane separation. The aim was to obtain optimum operation conditions, maximum methane production as well as overall performance of UMAS in treating sewage sludge, upon which further development on wastewater processes could be developed. Four steady states were attained as a part of this study that considered concentration ranges from 6500 to 2.300 mg/l for mixed liquor suspended solid (MLSS). UMAS was used to treat the sewage sludge at organic loading rates ranging from 0.06 to 0.12 kg COD /M3/day, and throughout the experiment, the removal efficiency of COD was from 79% to 93% and the methane gas percentage was between 93 and 85. The ammonia and nitrogen removal efficiency were 56 - 77 and 56 - 72 percentage respectively. The reactor pH is slightly changing during the experimental period with values around 6.8, 7.1, 7.2 and 7.00 in steady state 1, 2, 3 and 4, respectively. The slight changes in the alkalinity levels of pH indicate process stability. The gas volume was measured daily using a 20-litre displacement bottle. Biogas from sewage digester usually contain 55% to 65% of methane, 35% to 45% of carbon dioxide and < 1% nitrogen. Besides the main components, biogases also contain hydrogen sulphide and other sulphide compound, siloxanes, aromatic and halogenated compounds. The results obtained in this study have exposed the capability of ultrasonic assisted membrane anaerobic system (UMAS) in treating wastewater. Thus, using UMAS for the treatment is a challenging and interesting area; in this research work it is limited to study the steady states operation to provide continuous addition of feed solution (Raw sewage sludge) by gravity flow from feeder tank, which is on top of the reactor. In future, this study could be improved using specific type of ultrasonic against specific type of membrane anaerobic to increase the production methane, thus the performance of full process of UMAS will be increased and can produce more methane as well as it will reduce the time and cost. Further works are nevertheless required to provide deeper understanding of the mechanisms involved to facilitate the development of an optimum system applicable to the industry.